Reoperation for Pyriform Sinus Fistula in Pediatric Patients - Sheng, Qingfeng (Front Pediatr, 2020)
Introduction: The aim of this study was to analyze the authors' experience in re-operative surgery for children with pyriform sinus fistula (PSF) who were subjected to attempted but failed operations. Methods: We retrospectively analyzed the medical records of 30 patients with PSF who underwent reoperation (i.e., a revision of the primary performed definitive procedure) from January 2010 to December 2018. Results: There were 19 boys and 11 girls. Twenty-nine cases were left-sided. The median age of the patients when they underwent the primary operation was 5.5 years (range, 15 days−14 years). Five children received two definitive procedures from outside hospitals. The primary operations included traditional open-neck surgery (n = 30), endoscopic-assisted open-neck surgery (n = 4), and endoscopic laser cauterization (n = 1). The median time from primary operation to recurrence was 4 months (range, 1 month−4 years). The reasons for recurrence were incomplete resolution of infection (n = 7), incomplete resection of the fistula (n = 23), cauterization of PSF inner orifice (n = 1), only cyst excision in neonates (n = 2), and unknown (n = 2). All 30 children underwent endoscopy-assisted open-neck surgery. The median age of the children when they underwent reoperation was 8 years (range, 2–17 years). The fistula was detected in 29 cases (96.7%). After reoperation, good outcome was achieved in 27 patients (90%). Wound infection developed in one case. PSF recurred in two cases (6.7%). Conclusion: Most of the recurrences observed by us are preventable. Complete resolution of infection, clear verification, and exact resection of the fistula at a high level are essential for preventing recurrence. Endoscopy-assisted surgery is effective for PSF reoperation.